Różne znaczenia szkoły w filozofii a neokantyzm Leonarda Nelsona - Kubalica, Tomasz (Folia Philosophica, 2018)
The theme of the text is the interpretation of the philosophy of Leonard Nelson (1882—1927) and his place in the history of philosophy. The author asks whether his philosophy should be classified as Neo-Kantianism or outside its borders? In response to this question the author has developed his own instruments. On the one hand, he tried to determine the concept of Neo-Kantianism and thus, Fries’s reference to Kant; on the other hand, he applied the four-point scale for the classification of different philosophy communities and, in particular, the concept of philosophical school. In the light of these assumptions he has classified Nelson’s philosophy as psychological Neo-Kantianism.